Meningkatkan Aktivitas, Motivasi dan Hasil Belajar Melalui Penerapan Model Problem Based Learning pada Siswa Kelas XI MIPA 1 MAN Enrekang - Nurfadillah, Nurfadillah; Taiyeb, Mushawwir; Syamsiah, Syamsiah (Biology Teaching and Learning, 2020)
Abstract: This study aims to determine the increase in activity, motivation and student learning outcomes through the application of the model Problem Based Learning (PBL) in class XI MIPA 1 MAN Enrekang on cell material. This type of research is a classroom action research (CAR) which consists of 2 cycles. The subjects in this study were students of class XI MIPA 1 MAN Enrekang. The type of research instrument used was a learning activity observation sheet, a learning motivation questionnaire and a learning outcome test in the form of multiple-choice tests of 20 items for each cycle of cell material. The data obtained were analyzed statistically descriptive. The results showed that (1) there was an increase in the biology learning activities of students in class XI MIPA 1 MAN Enrekang namely classically from 66.47% increased to 80.03%, the amount of increase from cycle I to cycle II was 13.56%; (2) an increase in biology learning motivation of students in class XI MIPA 1 MAN Enrekang that is classically from 82.87% to 86.97%, the amount of increase from cycle I to cycle II is 4.11%; (3) an increase in biology learning outcomes of students in class XI MIPA 1 MAN Enrekang namely from 59.38% of students who completed to 96.88%, the number of increases from cycle I to cycle II was 37.50%. These results indicate that the application of the Problem Based Learning model can improve the activity, motivation and learning outcomes of students of the XI MIPA 1 MAN class Enrekang.Keywords: Problem Based Learning, activity, motivation and learning outcomes